A literatura e a bíblia : relações paratextuais em Os ambulantes de Deus - Olivo, Débora da Silva (2015)
This study analyses the paratextual relation between Literature and the Bible, in Hermilo Borba Filho’s text, Os ambulantes de Deus, and the Book of Exodus, from the Bible. It states the contribution of the mentioned author to the Brazilian literature, recognizing the possibility of studies related to him. It identifies the connexion between these texts, using Gerard Genette’s paratextual studies as its theoretical grounding, and attributing to the epigraphs the function of setting up these relations. It notes, in the epigraphs, the possibility of spreading the sense and the meaning of both texts, since literature intensifies the mythical aspects from the biblical narrative into its artistic content.